SAPOVIRUS AND ASTROVIRUS ACUTE GASTROENTERITIS IN THE REPUBLIC OF BELARUS - Shilova, Y.; Paklonskaya, N.; Amvrosieva , T.; Kaltunova , Yu.; Belskaya , I. (Eurasian Journal of Applied Biotechnology, 2022)
A significant variety of causative agents of acute gastroenteritis (AGE) of viral etiology dictates the need of studying their typical diversity and the contribution of the infections they cause, including little-studied ones, to the incidence. The aim of the presented work was to establish the frequency of astroviruses (HAsV) and sapoviruses (SaV) occurrence in patients with acute intestinal infections in our country, the characteristics of their circulation and genetic diversity. Astro- and sapovirus infections were detected in 3.0% and 2.3% of patients with AGE, respectively. Most often they were found in children aged 4-7, however, there were no significant differences in the frequency of their detection in patients of different age groups. Neither seasonal fluctuations in the circulation activity of these viral agents have been registered. The analysis of the genetic diversity of identified HAsV and SaV showed that the isolates identified in 2018-2021 belong to 2 HAsV genotypes - HuAsV-3, HuAsV-4 and to 3 SaV genotypes - GII.1, GI.2, GII.5. Taking into account the significant genetic variability of these pathogens, the ability to cause outbreaks and the likelihood of an increase in their activity, previously noted in other countries, it seems appropriate to monitor them in patients with AGE with the identification of detected genotypes by molecular methods.